Robot como esclavos modernos (Papeles, 2013)
Technology is an essential part of human lives. The drive for invention and technologicaldevelopment reached the idea and elaboration of artificial intelligence, whichis created in the image of man. The general attitude toward robots as main carriers ofthe artificial intelligence is very much alike to the master-slave relation described byAristotle is his Politics. Hegel in his Phenomenology of Spirit scrutinizes the masterslavedialectic. Historically, the tension between the two opposites leads to the processof transvaluation. In antiquity, the prevailing morality was the master’s one whilein Christianity the dominating moral values were the slave ones. Nietzsche offeredanother view on master-slave dialectic claiming ontologically speaking, masters arethe consciousness for itself and slaves are consciousness for another and this very factdefines their inferiority.